Legal Responsibility of Health Professionals in Protecting Patient Data - Lakoro, Danny Des Kartyko; Jumrati; Jamaludin, Ahmad (Research Horizon, 2025)
The protection of patient health data confidentiality is a fundamental aspect of the healthcare system, aimed at maintaining individual privacy rights. However, many medical data breaches still occur, posing risks to patients socially, psychologically, and legally. Therefore, regulations regarding healthcare professionals' obligations to maintain patient medical information have been clarified in Law No. 17 of 2023 on Health and the Code of Ethics for Health Professionals. This study examines the legal responsibility of healthcare professionals in maintaining patient health confidentiality and evaluates the obstacles and legal efforts made to enforce these regulations. The study uses a normative legal method by studying laws, legal concepts, and cases. Data were collected through a literature search that examined laws, legal books, and court decisions related to medical confidentiality breaches. This study found that regulations have clearly defined the obligations of healthcare professionals in maintaining patient medical data confidentiality. However, the implementation in the field still faces various obstacles, such as a lack of understanding among healthcare professionals regarding regulations, weak supervision systems, and challenges in enforcing the law for violators. Existing regulations have established severe sanctions for medical confidentiality breaches, but their effectiveness still needs to be strengthened through increased education for healthcare professionals, enhanced data security infrastructure, and more consistent monitoring and law enforcement.